Active wrapping paper against mango anthracnose fungi and its releasing profiles - Ratchadaporn Jaimun (2018)
Copyright © 2018 John Wiley & Sons, Ltd. Active wrapping papers varied in bio-based coating materials (chitosan and carboxymethyl cellulose) and vanillin concentrations (0.5%, 1.0%, 2.0%, and 4.0% (w/v)) were prepared to study their antifungal effects and release properties. Chitosan-coated paper with 1% (w/v) vanillin gave the best inhibition against mycelial growth of mango anthracnose fungi and could inhibit its conidiospores germination. The release of vanillin from a chitosan-coated paper under different conditions of temperatures (13°C, 25°C, and 37°C), relative humidity (RH) (75%, 86%, and 96% RH), and pH values (pH 3.8, 5.2, and 6.2) was studied. Moreover, the vanillin release from the paper to mango fruit under an actual commercial storage condition (13°C, 90% RH) was also investigated. The predominant mechanism of vanillin release under low temperatures (13-25°C) and all RH studied was a Fickian diffusion, whereas the high temperature (37°C) and in all buffers varying pH showed a non-Fickian behaviour. Increasing temperature and RH enhanced in diffusion coefficient (D value) from 78.24 × 10−10to 162.10 × 10−10 cm2/s and 42.87 × 10−10to 59.98 × 10−10 cm2/s, respectively. Meanwhile, the increasing pH value reduced the D value from 233.87 × 10−10to 122.74 × 10−10 cm2/s. The kinetic of vanillin release under an actual wrapping application exhibited a non-Fickian behaviour, and the D value was considerably low (approximately 65.36 × 10−12 cm2/s). The developed active wrapping paper can be great interest for food industry and is practically reasonable for postharvest mango fruits.